PELAKSANAAN PERJANJIAN DAN PENYELESAIAN WANPRESTASI PADA PERJANJIAN SEWA MENYEWA ANTARA PENGELOLA DENGAN PENYEWA RUSUNAWA DI KOTA PADANG SUMATERA BARAT - Khair, Umul; Ramadhona, Ana; Irhamni, Irhamni (Ensiklopedia of Journal, 2024)
Flats that have been inhabited by the community are also experiencing various problems even though management has been established, but there are still many who are not guaranteed to maintain the flats optimally. The implementation of the flat rental agreement between the manager and the tenant of the Simple Rental Flats (RUSUNAWA) in Padang City, West Sumatrera is carried out in written form and is required to complete the specified requirements, then the parties sign the agreement. Obstacles in implementing rental agreements for flats between managers and tenants of Rental Flats (RUSUNAWA) in Padang City, West Sumatrera are: some renters (the public) do not understand the contents of the agreement, the tenants. disorganized administration and the arrogance of some tenants when conveyed. The solution to the obstacles faced in implementing the agreement between the manager and the tenant of a simple rental flat (RUSUNAWA) in Padang City, West Sumatrera is: the management explains the contents of the draft agreement before it is signed by the tenant, and provides information and explanations needed by the tenant, namely the community, because the education level of the tenants is not the same.Keywords: Agreement, rental, tenant, management, RUSUNAWA